CLEAR CELL RENAL CANCER IN RENAL ALLOGRAFT: CASE STUDY AND LITERATURE REVIEW - R.R. AKHTYAMOV; S.V. FYODOROV; O.V. PYANKINA; E.D. KHADIEVA (Avicenna Tajik State Medical University, 2024)
A retrospective analysis of a patient with renal cell carcinoma (RCC) in renal allografts is presented, providing a comprehensive overview of the patient's medical history, the findings from various examinations, and the surgical interventions. The patient had end-stage renal disease due to nephrosclerosis following a kidney allotransplantation in 2008 and subsequently developed chronic allograft nephropathy. Upon examination, a tumor was discovered in the lower pole of the transplanted kidney. As a result of the end-stage renal transplant failure development, the patient underwent radical surgical treatment using advanced image-guided surgical techniques. This case is a compelling example of the critical importance of regular, thorough screenings for patients undergoing immunosuppressive therapy to identify any potential neoplastic processes promptly.